SIFAT ORGANOLEPTIK MIE BERBAHAN DASAR TEPUNG JAGUNG (Zea mays L.) TERNIKSTAMALISASI - Nastri Dila Saniati; Siti Nurdjanah; Susilawati -; Nanti Musita (Jurnal Teknologi & Industri Hasil Pertanian, 2013)
This research was dedicated to study the organoleptic properties of nixtamalized corn starch noodles and to find the best result from the duration needed in steeping process (0, 8, 16, 24, and 32 hours). The research was a single factor, arranged in a Complete Randomized Design (RAKL) with five replications. The data were analyzed using ANOVA and further tested with LSD at 5% level of of significance. The result showed that duration of nixtamalization had  significant effects on color and overall acceptance  of dry noodles as will as color of wet noodles. The best result was found on 8 hour of the steeping. This noodle had moisture content of 10.8% in the form of dry noodles and 62.1% in the form of wet noodles. It also contained 1.7% ash, 1.1% fat, 3.7% protein, 82.8% carbohydrate, 8.7% non starch polysaccharide, and 3.5% cooking loss. Keywords: corn noodles, nixtamalized corn flour